2014
DOI: 10.1155/2014/627181
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Protects against Hydrogen Peroxide‐Provoked Endothelial Dysfunction in Isolated Rat Aortic Rings: Implications for Antioxidant Therapy of Vascular Diseases

Abstract: Background and Objectives. Oxidative stress can initiate endothelial dysfunction and atherosclerosis. This study evaluated whether tetramethylpyrazine (TMP), the predominant active ingredient in Rhizoma Ligustici Wallichii (chuanxiong), prevents endothelial dysfunction in a rat model of oxidative stress. Methods. Isolated rat aortic rings were pretreated with various drugs before the induction of endothelial dysfunction by hydrogen peroxide (H2O2). Changes in isometric tension were then measured in acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The in vivo study revealed that atherosclerotic progression in ApoE -/mice was retarded by TMP, which is conformable to a previous study (20). Indeed, TMP exhibited some beneficial effects on atherosclerosis such as preventing endothelial dysfunction (19), regulating lipid levels in the plasma (20), attenuating oxidative stress (21), and inhibiting inflammation (22). In the present study, we further found that TMP decreased the expression of CD36 and SR-A and increased the expression of ABCA1 and ABCG1 in TMP-treated ApoE -/mice.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The in vivo study revealed that atherosclerotic progression in ApoE -/mice was retarded by TMP, which is conformable to a previous study (20). Indeed, TMP exhibited some beneficial effects on atherosclerosis such as preventing endothelial dysfunction (19), regulating lipid levels in the plasma (20), attenuating oxidative stress (21), and inhibiting inflammation (22). In the present study, we further found that TMP decreased the expression of CD36 and SR-A and increased the expression of ABCA1 and ABCG1 in TMP-treated ApoE -/mice.…”
Section: Discussionsupporting
confidence: 89%
“…Tetramethylpyrazine (TMP) has been recognized as a protective agent against atherosclerosis (19)(20)(21)(22). However, the effect and underlying mechanism by which TMP regulated lipid accumulation in macrophage-derived foam cells remained to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that TMP could relieve vascular tension and counteract oxidative stress by scavenging ROS, downregulating ERK1/MAPK signaling, and inhibiting NF- κ B. TMP can also protect vascular endothelial cells from H 2 O 2 -induced injury by increasing the content of phosphatidylcholine, reducing the release of arachidonic acid, and inhibiting the phosphorylation of cytosolic phospholipase A [ 143 , 144 ]. TMP, as an NADPH oxidase inhibitor and ROS scavenger, may be a potential antioxidant drug for the treatment of heart failure [ 145 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Tetramethylpyrazine (TMP) is an alkaloid monomer that exists in the roots or stems of the Chinese herbal medicine, Ligusticum wallichii (9). Previous studies have reported that TMP primarily acts as an antioxidant, calcium antagonist, inhibitor of platelet aggregation, promoter of microcirculation and blood clots, and regulator of the immune response (10,11).…”
Section: Introductionmentioning
confidence: 99%